Corporate Fundamentals, Bi Rate And Systematic Risk: Evidence From Indonesia Stock Exchange - Nita Puspitasari, Perdana Wahyu Santosa, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The aim of this study is to understand the effect of company's fundamental factors and BI rate on systematic risk (beta) on the Indonesia Stock Exchange (IDX).Ã‚Â In portfolio theory, there are two types of risk, namely systematic risk and non-systematic risk.Ã‚Â The focus of this study is on systematic risk which was measured through beta (ÃŽÂ²), where each stock had a different beta.Ã‚Â The analyses used independent variables ofÃ‚Â sales growthÃ‚Â (SG),Ã‚Â net profit marginÃ‚Â (NPM),Ã‚Â debt to equity ratioÃ‚Â (DER) and BIÃ‚Â rateÃ‚Â (benchmark interest rate) on stock beta.Ã‚Â The data used were quarterly data ofÃ‚Â issuers listedin the LQ-45 index in theÃ‚Â period of 2009-2016 which were analysed usingÃ‚Â panel data regressionÃ‚Â method.Ã‚Â The conclusion from panel data analysis ofÃ‚Â LQ-45 indexÃ‚Â is that SG, NPM and DER contribute a significant impactÃ‚Â onÃ‚Â systematic risk,Ã‚Â but the macroeconomic proxy, namelyBIÃ‚Â rate, does not offerÃ‚Â significant influence on stock betaÃ‚Â (ÃŽÂ²).Implication: corporate fundamental factors such as sales growth, net profit margin and solvency has effect significantly on beta (ÃŽÂ²), however BI rate does not.